Gellan Gum-Based Bilayer Mucoadhesive Films Loaded with Moxifloxacin Hydrochloride and Clove Oil for Possible Treatment of Periodontitis - Li A; Khan IN; Khan IU; Yousaf AM; Shahzad Y (Dove Medical Press, 2021)
Aiqin Li,1 Ifrah Nabi Khan,2 Ikram Ullah Khan,2 Abid Mehmood Yousaf,3 Yasser Shahzad3 1Department of Stomatology, Zhengzhou Central Hospital Affiliated to Zhengzhou University, Zhengzhou, People's Republic of China; 2Department of Pharmaceutics, Faculty of Pharmaceutical Sciences, Government College University Faisalabad, Faisalabad, Pakistan; 3Department of Pharmacy, COMSATS University Islamabad, Lahore, PakistanCorrespondence: Yasser ShahzadDepartment of Pharmacy, COMSATS University Islamabad, Lahore Campus, Lahore, PakistanEmail y.shahzad@live.comIkram Ullah KhanDepartment of Pharmaceutics, Faculty of Pharmaceutical Sciences, Government College University Faisalabad, Faisalabad, PakistanEmail ikramglt@gmail.comBackground/Objective: Periodontitis is a widely spread oral infection and various antibiotics are utilized for its treatment, but high oral doses and development of antibiotic resistance limit their use. This study was aimed at development of natural polymer-based mucoadhesive bilayer films loaded with moxifloxacin hydrochloride (Mox) and clove essential oil (CEO) to potentially combat bacterial infection associated with periodontitis.Methods: Films were synthesized by double solvent casting technique having an antibiotic in the gellan gum-based primary layer with clove oil in a hydroxyethyl cellulose-based secondary layer.Results: Prepared films were transparent, flexible, and showed high antibacterial response against both gram-positive and gram-negative bacteria. The films showed excellent pharmaceutical attributes in terms of drug content, folding endurance, swelling index, and mucoadhesive strength. Solid state characterization of formulation showed successful incorporation of drug and oil in separate layers of hydrogel structure. An in-vitro release study showed an initial burst release of drug followed by sustained release for up to 48 hours.Conclusion: The prepared mucoadhesive bilayer buccal films could be used as a potential therapeutic option for the management of periodontitis.Keywords: gellan gum, hydroxyethyl cellulose, bilayer films, mucoadhesive, moxifloxacin hydrochloride, clove oil